Enhancing solar irrigation pump adoption through effective training in Nepal - Gautam, K.; Shrestha, Shisher; Rauniyar, Amrita; Mishra, Anuj (International Water Management Institute, 2025)
Capacity building is vital to sustain Nepal’s growing demand for solar irrigation pumps (SIPs). From 2021 to 2024, seven training programs on operations and maintenance (O&M) were held across the Terai, engaging local technicians, government representatives, and technical students. With 41% female participation, the program addressed gender gaps in agriculture driven by male outmigration. Post-training surveys show participants gained confidence, diversified skills, and in many cases increased income. Feedback highlights the need for longer, more practical training and advanced packages for engineers. Strengthening local capacity is key to reliable SIP adoption and inclusive clean energy transitions in agriculture.